Penerapan Ekonomi Sirkular Dalam Penanganan Sampah Di Kabupaten Sumbawa Barat - Rita Ekawati; Sri Rahayu (Program Studi Manajemen Fakultas Ekonomika dan Bisnis Universitas Majalengka, 2025)
The increasing volume of waste in West Sumbawa Regency has become a pressing issue, driven by population growth, urbanization, and changing consumption patterns that continue to generate more waste, while the capacity of the Final Processing Site (TPA) is limited and nearing its maximum threshold. This study aims to analyze the current waste management practices in West Sumbawa Regency, examine external factors influencing the application of a circular economy in waste handling using the PESTELC approach, and develop recommendations for a circular economy model in waste management through a descriptive qualitative method, with data analyzed using the Miles and Huberman model and verified through triangulation. The findings reveal that the current waste management system still follows a linear “collect-transport-dispose” model, with the Batu Putih Final Processing Site operating through open dumping and limited waste processing, resulting in inadequate waste management both upstream and downstream. Institutional structures are not yet optimally organized, transportation facilities are insufficient, and the concept of a circular economy has not been implemented. The PESTELC analysis shows that the implementation of a circular economy is still hindered by non-specific policies, limited funding and market access, low public awareness, lack of appropriate technology adoption, and weaknesses in legal frameworks and competition. The recommended circular economy model proposes a transition from the current linear system to a sustainable and collaborative circular system, aimed at improving environmental quality and creating new economic opportunities for the local community.